Towards edible oil self-sufficiency in Ethiopia: Lessons and prospects - Getinet Alemaw; Fekadu Gurmu (Cogent Food & Agriculture, 2023)
AbstractNine oilseeds namely noug, gomenzer, linseed, soybean, sunflower, castor, sesame, ground nut and cotton are important in Ethiopia for edible oil consumption. During the last 60 years, 156 varieties with their production practices were registered. Sesame contributes significantly to the foreign currency earnings next to coffee. Despite the revenue from export, 90% of the national demand of edible oil is imported. Among oilseeds, groundnut, sunflower and soybean are the choice of cultivation both in high rainfall Western lowlands and irrigated areas of Awash, Omo and Wabe Shebelle and Dawa Genale valleys. Similarly, sesame exports can be doubled or tripled using irrigated production. In addition, soybean can be cultivated as a source of raw material for food and feed industries. Oil palm occupies small areas compared to other oil seeds but contributes half for global consumption. In the short term, sufficient amount of edible oil to meet the national demand can come from maximizing sesame export and production of sunflower, groundnut and soybean as raw material for local industries. In the long term, oil palm production is indispensable to feed the ever-growing population. Therefore, the ultimate solution for edible oil self-sufficiency for most customers can only come from the high-yielding perennial oil palm with high yield and less production cost.